(untitled) (The Agriculturists, 2010)
An experiment was conducted at the Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh, Bangladesh to evaluate the influence of fertilizer-N on biochemical characteristics, nutrient accumulation and yield of potatoes during the period from November 2002 to March 2003. Two varieties, namely Cardinal and Diamant and five levels of N viz. 0, 100, 125, 150 and 175 kg ha-1 were applied in a factorial randomized complete block design with three replications. The results indicated that the biochemical characteristics, nutrient concentrations, yield components and yield were significantly influenced by the different levels of N. The nitrate reductase activity, chlorophyll content, total free amino acid showed positive linear relationship with different doses of N-fertilizers. The highest tuber weight and nitrogen accumulation were found from the plants which received 150 kg N ha-1. Application of 150 kg N ha-1 resulted in best biochemical characteristics, nutrient uptake, yield and yield components of potato varieties- Cardinal and Diament.